Design of Intelligent Internet of Things for Equipment Maintenance - Xu Xiaoli; Zuo Yunbo; Wu Guoxin (2011 International Conference on Intelligent Computation Technology and Automation, 2011)
In order to strengthen the security guarantee and improve the scientific management level of important equipments, the intelligent internet of things for equipment maintenance (IITEM) was presented in this paper. IITEM collects the static and dynamic information of electrical and mechanical equipments by all kinds of sensors, and standardizes various types of information, so as to suit the information transmission needs of the Internet of Things. According to the characteristics of mechanical and electrical equipment, IITEM makes intelligent processing of device information, including establishment of signal sample database and knowledge base, extraction of running status feature of complex equipment, state analysis, model building, fault diagnosis, fault prediction, etc. Centering on the functional objectives of IITEM, the demonstration project of IITEM was designed. It could realize online safety monitoring, fault prediction and comprehensive protection of key equipment groups, avoid economic losses and casualties, extend equipment maintenance cycle, and promote establishment of coding system, standards and norms related to the intelligent internet of things for equipment maintenance, which should be suitable for the Chinese Internet of Things.